Self-Presentation of Cashless Users through OVO E-Wallet (Study on Students of PGRI University Palembang) - Ayu Zahra Ramadhani (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This article examined how self-presentation was presented by cashless users through OVO e-wallet for student in PGRI Palembang. This research used descriptive qualitative method. Data collection techniques used by author were observation in PGRI University, interview with user OVO and did documentation when student used OVO. The author found the background of PGRI student was using OVO including policies regarding cashless, personal choices and social environment. This article used self-presentation theory by Erving Goffman to analyze PGRI student self-concepts in using OVO. As the results, this study has been shown that student display slang self-concepts such as student was hanging out in cafes and malls, contemporary self-concepts such as student was paying for all types of entertainment using OVO payment applications and socialite self- concepts such as student was buying clothes and accessories to support their appearance in front of his friends. It reflects that student adopt urban and hedonistic lifestyles when using OVO so that the assessment of their peers considers that students who are just hanging out for chasing discounts, current students are actually consumptive and socialite student are only for social climbing in class.